Isotope dilution determination for the trace level of 4(5)-methylimidazole in beverages using dispersive liquid-liquid microextraction coupled with ESI-HPLC–MS/MS. (15th April 2018) - Feng, Ting-Ting; Wu, Jian-Hai; Liang, Xu; Du, Ming; Qin, Lei; Xu, Xian-Bing
Highlights: DLLME first coupled with HPLC–MS/MS for 4(5)-methylimidazole analysis in beverages. DLLME method validated by stable isotope label technique. The established method was simple, rapid and reliable. Abstract: In this study, a rapid and reliable pretreatment method called dispersive liquid-liquid microextraction (DLLME) was developed for the determination of 4(5)-methylimidazole (4-MeI) in beverages. The clean-up samples were analyzed by a high performance liquid chromatography coupled with triple quadrupole mass spectrometer (HPLC–MS/MS) using a reversed-phase C18 column (250 mm × 4.6 mm, 5 μm). The matrix effects and the fault of DLLME operation were corrected by the isotope dilution technique. The developed method exhibited the limit of quantification (0.3 μg L −1 ) and excellent linearity (R 2 = 0.999). In addition, the recovery values of 4-MeI in carbonated beverage were ranging from 102.60% to 113.22%, in soft drinks were ranging from 103.24% to 108.85%. The content 4-MeI was detected in thirteen beverage samples treated with DLLME and solid phase extraction method (SPE) (ranging from 6.4 to 165.5 μg L −1 ). The consistent result of 4-MeI content detected by DLLME and SPE method concluded that the established method on the basis of DLLME was rapid, robust and accurate for the trace 4-MeI determination in beverages.